2019
DOI: 10.1029/2019jd031149
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Resolved Characterization of the Chromophores in Atmospheric Particulate Matter From a Typical Coal‐Burning City in China

Abstract: This study reports the size‐resolved characterization of the chromophores in atmospheric particulate matter in Linfen, a typical coal‐burning city in China. The optical properties of both the water‐soluble and water‐insoluble chromophores in atmospheric particulates are studied using excitation‐emission matrix spectroscopy and follow the parallel factor analysis of excitation‐emission matrix data. The mass absorption efficiency and normalized fluorescence volume by mass concentration of the organic carbon in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 60 publications
(100 reference statements)
6
41
0
Order By: Relevance
“…3.2 of this study, this particulate matter is related to combustion, which indicates that coal combustion in winter may provide an important contribution to EPFRs. The EPFR concentration in the fine PM of Linfen reported above is equivalent to that in the fine PM of Xi'an, but it is 10 times smaller than that in the fine PM of Beijing (Yang et al, 2017;Chen et al, 2019b). Although the particle size distribution characteristics of EPFRs in winter and summer are different, their concentration levels are similar, which in- dicates that the EPFR concentration is not related to the PM concentration but is determined by the source characteristics.…”
Section: Epfr Exposure Evaluationmentioning
confidence: 80%
See 2 more Smart Citations
“…3.2 of this study, this particulate matter is related to combustion, which indicates that coal combustion in winter may provide an important contribution to EPFRs. The EPFR concentration in the fine PM of Linfen reported above is equivalent to that in the fine PM of Xi'an, but it is 10 times smaller than that in the fine PM of Beijing (Yang et al, 2017;Chen et al, 2019b). Although the particle size distribution characteristics of EPFRs in winter and summer are different, their concentration levels are similar, which in- dicates that the EPFR concentration is not related to the PM concentration but is determined by the source characteristics.…”
Section: Epfr Exposure Evaluationmentioning
confidence: 80%
“…EPFRs of different lifetimes are present in atmospheric PM, with only a few hours for short-lifetime EPFRs and several years for longlifetime EPFRs that show no signs of decay (Gehling and Dellinger, 2013;Chen et al, 2019c). Most studies indicate that sources of transportation and combustion may be the primary EPFR sources in atmospheric PM (Wang et al, 2018;Yang et al, 2017;Chen et al, 2019b). Chen et al (2018bChen et al ( , 2019b found that strong atmospheric photochemical effects in summer and dust particles may also be important sources of EPFRs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EFs emitted from bituminous CC (PM = 9.1 × 10 −1 ± 6.5 × 10 −1 g kg −1 fuel, OC = 4.2 × 10 −1 ± 3.3 × 10 −1 g kg −1 fuel, and EC = 9.4 × 10 −2 ± 1.9 × 10 −1 g kg −1 fuel) were much higher than those of anthracite combustion (PM = 1.5 × 10 −1 ± 8.9 × 10 −2 g kg −1 fuel, OC = 1.2 × 10 −2 ± 4.5 × 10 −3 g kg −1 fuel, and EC = 1.6 × 10 −4 ± 1.4 × 10 −4 g kg −1 fuel) in the same stove. These differences could be attributed to the high volatile matter content of bituminous coal (Tian et al, 2017;Chen et al, 2005). Note that the CC smoke collection began when the flame had been ignited with one third of the material, and the rest was added.…”
Section: Emission Characteristics and Light Absorption Of Extractsmentioning
confidence: 99%
“…The C5 and C6 components were more intense in vehicle exhaust particles (25 ± 6.8 % and 50 ± 6.8 %, respectively), suggesting they were the primary vehicle emission chromophores. The last study observed that the relative abundances of various chromophores in aerosols with different particle sizes were different (Chen et al, 2019). Therefore, the fluorescence technique is sensitive for chromophores with different sources, sizes, and chemical structures, and so on.…”
Section: Eem Spectra Of Wsoc and Msocmentioning
confidence: 99%